Has COVID-19 brought a temporary halt to overtourism? - Tiwari, Pinaz; Chowdhary, Nimit (Turyzm/Tourism, 2021)
COVID-19 has caused radical changes in the lives of people as well as economies. These changes are deemed as evolutionary and would bring a new phase of transformation. However, current practices of both people and businesses might cease once the crisis disappears. In the tourism context, going back to unsustainable and irresponsible practices would lead to the re-emergence of tourism aversion. This research note addresses the possibility that COVID-19 has only brought a temporary halt to the pre-existing issue of over-tourism and its related unsustainable practices. Even though the travel restrictions imposed by several countries amidst the spread of coronavirus have created a situation of “zero tourism”, the tourism sector has now resumed its operations in most of the world. By presenting a conceptual framework, this note stresses that if the sector continues to act in the same way as before the virus, the situation of overtourism will re-emerge in the post-COVID-19 phase. Therefore, to prevent this issue, emphasising quality tourism, inculcating responsible behaviour, and the incorporation of technology are suggested.